2017
DOI: 10.5005/jp-journals-10028-1229
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Early-onset Glaucoma following Pediatric Cataract Surgery in Egyptian Children: A One-year Study

Abstract: AimTo study the incidence and risk factors of glaucoma occurring within 1 year following pediatric cataract surgery in Egyptian children.Materials and methodsThis is a prospective nonrandomized study conducted at Aburich Children’s Hospital, over a period of 1 year on a cohort of Egyptian patients with congenital and infantile cataract. One hundred and fifty eyes of 88 patients were enrolled in this study. All the patients underwent anterior approach removal of lens matter, whereas primary intraocular lens (IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…However, fully developed secondary glaucoma was seen in only 7% (n = 8/110), whereas glaucoma suspect was seen in 3% (n = 3/110) and OHT in 9% (n = 10/110), reflecting the literature. 17,21,22,27,28 The rate of bilateral involvement was significantly higher in the IOP group (72%; non-IOP: 42%), which reflects the literature. 18 In bilateral cataract cases several underlying causes such as congenital infections (such as TORCH), or drug exposure have to be ruled out.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, fully developed secondary glaucoma was seen in only 7% (n = 8/110), whereas glaucoma suspect was seen in 3% (n = 3/110) and OHT in 9% (n = 10/110), reflecting the literature. 17,21,22,27,28 The rate of bilateral involvement was significantly higher in the IOP group (72%; non-IOP: 42%), which reflects the literature. 18 In bilateral cataract cases several underlying causes such as congenital infections (such as TORCH), or drug exposure have to be ruled out.…”
Section: Discussionsupporting
confidence: 81%
“…However, fully developed secondary glaucoma was seen in only 7% ( n = 8/110), whereas glaucoma suspect was seen in 3% ( n = 3/110) and OHT in 9% ( n = 10/110), reflecting the literature. 17,21,22,27,28…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 22.2% of the glaucoma cases in the IOL group had an IOL placed in the ciliary sulcus (10) . Gawdat et al (25) reported that most cases of glaucoma occur during the first year of follow-up, and its incidence was higher in aphakic eyes than pseudophakic eyes (77% vs. 22%, respectively). Haargaard et al (26) showed that glaucoma cases continued to occur even >10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found the risk of secondary glaucoma to be between 0% and 58% following congenital cataract surgery, but the risk varies with differences in the study population, the definition of glaucoma and the length of follow‐up (Chen et al., 2006, Gawdat et al. (n.d.); Haargaard et al., 2008, Sachdeva et al., 2016; Solebo & Rahi, 2020, Wang et al., 2020). In studies including older children up to 14 years at the time of cataract surgery, the risk of developing secondary glaucoma was 2%–23.7% when the children had a mean follow‐up time between 1 and 5 years (Beheshtnejad et al., 2022; Freedman et al., 2020; Magnusson et al., 2000; Nyström, Haargaard, et al., 2020; Repka et al., 2022; Tatham et al., 2010; Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%